Ilmu dan Agama dalam Kurikulum Pendidikan Islam Multidispliner - Asma; Kasim Yahiji; Syarifuddin Ondeng; Nadjamuddin Petta Solong (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
This paper discusses the role of Islamic education within a multidisciplinary curriculum that integrates various disciplines to provide a more comprehensive understanding of Islamic teachings. This multidisciplinary approach is considered essential in addressing the challenges of modern times, particularly in Islamic Religious Education (IRE). By utilizing multiple perspectives, it is expected that students will gain broader and deeper knowledge not only in religious contexts but also in social, cultural, and scientific aspects. The research method used in this paper is literature review, where various academic sources and theories of Islamic education are examined to understand the application of the multidisciplinary approach in education. The findings indicate that a multidisciplinary curriculum in IRE can help shape students' character holistically, encompassing spiritual, moral, and intellectual dimensions.